2011
DOI: 10.1007/s00726-011-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transform analysis of NMR structure ensembles to reveal internal fluctuations of enzymes

Abstract: Internal motions and flexibility are essential for biological functions in proteins. To assess the internal fluctuations and conformational flexibility of proteins, reliable computational methods are needed. In this study, wavelet transformation was used to filter out the noise and facilitate investigating the internal positional fluctuations of enzymes within nuclear magnetic resonance (NMR) structure ensembles. Moreover, potential active sites were identified by combining with positional fluctuation score, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Interchanges between these fields during the last 20 years have led to many new wavelet applications, especially image processing and de-noising noisy data. Wavelets have also been employed in various tasks to do with NMR signal processing ( Barache et al , 1997 ; Dancea and Güntert, 2005 ; Gronwald and Kalbitzer, 2004 ; Günther et al , 2000 , 2002 ; Hu et al , 2011 ; Lang et al , 1996 ; Neue, 1996 ; Shao et al , 2000 ). Such tasks include analyzing the dynamical behavior of NMR signals ( Barache et al , 1997 ; Hu et al , 2011 ; Neue, 1996 ), de-noising the NMR spectra ( Dancea and Güntert, 2005 ; Günther et al , 2000 ), suppressing water peaks from the spectra ( Gronwald and Kalbitzer, 2004 ; Günther et al , 2002 ), and increasing the resolution of the spectra ( Shao et al , 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interchanges between these fields during the last 20 years have led to many new wavelet applications, especially image processing and de-noising noisy data. Wavelets have also been employed in various tasks to do with NMR signal processing ( Barache et al , 1997 ; Dancea and Güntert, 2005 ; Gronwald and Kalbitzer, 2004 ; Günther et al , 2000 , 2002 ; Hu et al , 2011 ; Lang et al , 1996 ; Neue, 1996 ; Shao et al , 2000 ). Such tasks include analyzing the dynamical behavior of NMR signals ( Barache et al , 1997 ; Hu et al , 2011 ; Neue, 1996 ), de-noising the NMR spectra ( Dancea and Güntert, 2005 ; Günther et al , 2000 ), suppressing water peaks from the spectra ( Gronwald and Kalbitzer, 2004 ; Günther et al , 2002 ), and increasing the resolution of the spectra ( Shao et al , 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wavelet transform (WT) has been successfully applied for chemical signal processing [20][21][22][23][24]. It has been shown that a signal can be represented by a very small number of wavelet functions, giving an efficient expression due to the orthogonality of wavelet functions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, computational community has played more and more important roles to simplify and accelerate this tedious structure determination process 2 3 4 5 6 7 8 9 . Peak picking has been treated as a signal processing problem and has been tackled by a variety of methods 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 . Resonance assignment, on the other hand, is often formulated as a graph-based problem to find the best mapping between spin systems and residues of the target protein.…”
mentioning
confidence: 99%